Trophic ecology of Hemichromis fasciatus (Pisces: Cichlidae: Perciformes) from Opkara stream, Oueme river, Northern Benin: needs for species management and rational exploitation - SIDI IMOROU, Rachad; ADITE, ALPHONSE; SONON, Pejanos Stansilas; ARAME, Hamidou; ADJIBADE, Kayode Nambil (My University, 2020)
The carnivorous cichlid Hemichromis fasciatus (Peters, 1852) displays a wide distribution in the freshwaters and brackish waters of Tropical Africa and particularly in the West African water bodies. In the Okpara stream of the Oueme River in Benin, Hemichromis fasciatus is the dominant fish species making numerically 29.20% of the fish community. We investigated on the feeding ecology of this cichlid to evaluate the level of predation and impact on the Okpara stream fish community. Hemichromis fasciatus individuals were sampled monthly from December 2015 to May 2017 using an experimental gill net and a seine. The dietary analysis showed that H. fasciatus foraged mainly on fishes that made 61.212% of the diet, but also ingested aquatic insects (26.8%), zooplankton (2.721%), and detritus (4.09 %). H. fasciatus showed a moderate diet breadth ranging between 1.20 and 13.77 (mean =5.7) and diet overlaps among size categories varied between Øjk=0.21 and Øjk=1, indicating an ontogenetic diet shift. The study revealed an eco-morphological trend of the feeding habit indicated mainly by the increase of fish consumption with SL (r=0.52) and GL (r=0.68), the increase of detritus consumption with GL (r=0.332) and the decrease of zooplankton consumption with SL (r=0.648) and GL (r=-0.51). H. fasciatus displayed a trophic flexibility behavior that favored seasonal and spatial diet variations. The piscivorous feeding trend was also shown by the relative gut length (GL/SL = 0.73) that fall in the carnivorous range. The dominance of H. fasciatus and its high level of predation depicted in this study constitute a threat for the fish community. The implementation of a rational management and exploitation scheme of this carnivorous cichlid is required to guaranty a balanced food web and the survival of the Okpara stream fish community.
Keywords: Eco-morphology; Hemichromis fasciatus; management; Okpara stream; piscivore